Queer Theory, Visual Culture, and Emotional Resistances in Torremolinos (Spain) during the Sixties and Seventies. - Cuevas-del-Barrio, Javier (My University, 2019)
This paper proposes an epistemological approximation between the method of visual analysis developed by Aby Warburg in Atlas Mnemosyne, based on concepts such as Nachleben der Antike (the afterlife of Antiquity) and Pathosformel, (the “emotionally charged visual tropes”), and some aspects of the Queer Theory, in particular the concept of "emotional resistances" proposed by Eve Kosofsky Sedgwick with the intention of developing "reparative epistemologies".
Keywords: Teoría Queer; Queer Theory; Eve Kosofsky Sedgwick; Aby Warburg